Synergistic effects of D-arginine, D-methionine and D-histidine against Porphyromonas gingivalis biofilms. Issue 2 (22nd February 2021) - Zhang, Zhenyang; Li, Baosheng; Cai, Qing; Qiao, Shuwei; Wang, Dan; Wang, Heling; Zhang, Huiyan; Yang, Yalan; Meng, Weiyan
Abstract: Porphyromonas gingivalis biofilms are implicated in the pathology of peri-implantitis and periodontitis. In this study, D-arginine (R), D-methionine (M), D-histidine (H), and a mixture of these D-amino acids (D-AAs) were investigated as an effective therapeutic strategy against P. gingivalis biofilms. The bacterial growth activity and minimum inhibitory concentrations were determined for each D-AA, along with the effects of the D-AAs mixture on biofilm development, morphology, structure, extracellular polysaccharides (EPS), cytotoxicity towards commensals, and bacterial structure. The D-AA mixture delayed the proliferation of P. gingivalis, changed its membrane structure, and decreased biofilm thickness and integrity, as compared with individual D-AAs. The EPS content increased with the concentration of D-AAs. The present study shows that a 4 mM RMH, triple D-AA mixture, enhanced deleterious effects on P. gingivalis biofilms without any cytotoxicity compared with individual D-AAs, thus providing a new strategy for the treatment of peri-implantitis and periodontitis.